UZBEKISTAN’S COOPERATION WITH FOREIGN COUNTRIES IN PROTECTING A HEALTHY FAMILY AND ITS RESULTS - Kholikov Golib (Galaxy International Interdisciplinary Research Journal, 2022)
The article examines the work of Uzbekistan with foreign countries under the program of healthy families and healthy children. In the first years of independence, special attention was paid to the cooperation of international organizations in the work and development of health care in the republic, the peculiarity of this process is that it was signed with a number of developed countries.